A New Approach for Refractive Index of Binary Liquid Mixture - Saxena, M.C.; Dubey, Poonam; Tripathi, Ashutosh (Asian Journal of Chemistry, 2010)
In the present work a comparative study of five mixing rules of refractive index has been carried out to test their validity for nine binary liquid mixtures at 313.5 K. All the mixing rule perform well within the limit of experimental error but the performance of Lorentz-Lorenz (L-L) and Gladstone-Dale(G-D) relation is comparatively better than those of others. A new approach has also given satisfactory results which can be successfully use to predict the refractive index of the binary liquid mixture which requires only refractive index of its pure component.